Understanding Customer Perception of Airline Service Quality and Brand Image: A Pathway to Loyalty and Repurchase Intentions - Astri Rumondang Banjarnahor; Juliater Simarmata; Rudi Max Damara Gugat; Otto Sugiharto Prakoso; Andre Yosafat (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates how customer perceptions of service quality and airline brand image affect customer loyalty and intentions to repurchase. By employing a systematic literature review (SLR) method in line with the PRISMA protocol, the research examines 50 articles indexed in Scopus that pertain to customer perceptions in the airline sector. The results indicate that favorable perceptions of service quality significantly impact brand image, thereby promoting customer loyalty and repurchase intentions. Mediating factors such as "brand love," "passenger loyalty," and "positive word of mouth" are essential in reinforcing these connections. Additionally, the study presents a conceptual framework for airlines to develop more effective strategies aimed at improving customer loyalty. This research not only addresses theoretical gaps but also provides practical insights for enhancing airline service strategies that yield long-term benefits for customer loyalty.